Faktor Faktor yang Berhubungan dengan Kejadian Putus Obat pada Pasien Tuberkulosis Paru di Rumah Sakit Bhakti Asih Tangerang - Yulianti Yulianti; Ekbert Mandaku; Tanto Tanto; Dessi Juwita (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2025)
Background: Pulmonary Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis, primarily affecting the lungs and spreading through airborne droplets. According to the World Health Organization (WHO) 2020, tuberculosis remains a significant global health challenge and requires ongoing efforts for its control as part of the Sustainable Development Goals (SDGs). Objective: This study aims to identify the factors associated with medication non- compliance in pulmonary tuberculosis patients at Bhakti Asih Hospital, Tangerang, focusing on age, gender, knowledge about tuberculosis, medication side effects, and family support. Methods: A quantitative approach was employed, using primary data from questionnaires in a field research method. The sample consisted of 40 patients diagnosed with pulmonary tuberculosis. Data were collected through interviews and analyzed using Chi-Square tests to examine the relationship between independent variables and medication non-compliance. Results: The Chi-Square test revealed significant associations between age (p = 0.038), knowledge (p = 0.033), medication side effects (p = 0.049), and family support (p = 0.027) with medication non-compliance. Gender (p = 0.62) did not show a significant association, although males were found to have a 4.037 times greater risk of non- compliance compared to females. Conclusion: Factors such as age, knowledge about tuberculosis, medication side effects, and family support are significantly associated with medication non-compliance in pulmonary tuberculosis patients at Bhakti Asih Hospital, Tangerang. Recommendation: Health education should focus on improving patient knowledge and managing medication side effects. The role of family support should also be strengthened to enhance patient adherence to tuberculosis treatment.